An epidemic of dengue-1 in a remote village in rural Laos. - Audrey Dubot-Pérès; Phengta Vongphrachanh; Justin Denny; Rattanaphone Phetsouvanh; Singharath Linthavong; Bounthanom Sengkeopraseuth; Amphai Khasing; Vimattha Xaythideth; Catrin E Moore; Manivanh Vongsouvath; Josée Castonguay-Vanier; Bountoy Sibounheuang; et al. (Public Library of Science (PLoS), 2013)
In the Lao PDR (Laos), urban dengue is an increasingly recognised public health problem. We describe a dengue-1 virus outbreak in a rural northwestern Lao forest village during the cool season of 2008. The isolated strain was genotypically "endemic" and not "sylvatic," belonging to the genotype 1, Asia 3 clade. Phylogenetic analyses of 37 other dengue-1 sequences from diverse areas of Laos between 2007 and 2010 showed that the geographic distribution of some strains remained focal overtime while others were dispersed throughout the country. Evidence that dengue viruses have broad circulation in the region, crossing country borders, was also obtained. Whether the outbreak arose from dengue importation from an urban centre into a dengue-naïve community or crossed into the village from a forest cycle is unknown. More epidemiological and entomological investigations are required to understand dengue epidemiology and the importance of rural and forest dengue dynamics in Laos.